Perancangan Dan Pembuatan Smart Distribution Pada Gudang Penyimpanan Bumbu Dapur Dengan Menggunakan Delphi 7 Sebagai Pusat Instruksi Dan Pengolahan Data - Ega Firsty Ayu Pratiwi; Retno Devita; Okta Andrica Putra (Prodi Sistem Informasi Universitas Dharma Andalas, 2022)
Kitchen spices are substances that generally come from flavorful plants that are added to dishes for the purpose of flavoring food. Seasonings serve to give food a better taste. With so many types of spices, storage in the warehouse is needed a place that fits the types of spices. So that the supply is not confused to store kitchen spices and if needed is not confused anymore. The supplier will send spices according to consumer demand. In this way, if the spices are used up, Delphi will automatically instruct the speakers and cameras to monitor the supply to enter the spices. What has been determined by consumer demand is how many spices are needed and a data base to collect data. RFID as taking customer data by using an ID card to enter the kitchen spice storage warehouse. Loadcell as measuring the weight of the weigher.